(untitled) (Journal of Engineering, 2019)
This paper aims to study the second-order geometric nonlinearity effects of P-Delta on the dynamic response of tall reinforced concrete buildings due to a wide range of earthquake ground motion forces, including minor earthquake up to moderate and strong earthquakes. The frequency domain dynamic analysis procedure was used for response assessment. Reinforced concrete building models with different heights up to 50 stories were analyzed. The finite element software ETABS (version 16.0.3) was used to analyze reinforced concrete building models. The study reveals that the percentage increase in buildings’ sway and drift due to P-Delta effects are nearly constant for specific building height irrespective of the seismic design category assigned to the building. Generally, increase in building lateral displacement and story drift due to P-Delta effects for all seismic design categories is less than 2% for 10 story buildings, whereas this increase for 20 stories or taller buildings is significant with a maximum value around 16% for 50 story building. As for column forces, the study shows that, generally, columns bending moment increases and shear force decreases when P-Delta effects accounted for. In conclusion, the study recommended that the effects of P-Delta need to be addressed for all SDCs allowed by ASCE7-10 and the most important factor to abandonment P-Delta effects is the building height limit.